Book Reviews (The Australian journal of anthropology, 1985)
Book reviewed in this article: The Human Primate. By R. E. Passingham Ethology. By Robert A. Hinde The Monkey Puzzle, A Family Tree. By John Gribbin & Jeremy Cherfas Man, the Tottering Biped. The Evolution of his Posture, Poise and Skill. By Phillip V. Tobias Paradoxes of Evolution in Recent Man. By D. F. Roberts Raymond Arthur Dart: A Pictorial Profile. Professor Dart's Discovery of ‘The Missing Link’. By Frances Wheelhouse Darwin. By Wilma George The Ethnography of Cannibalism. Edited by Paula Brown and Donald Tuzin Magicians of Manumanua: Living Myth in Kalauna. By Michael W. Young Sound and Sentiment. Birds, Weeping, Poetics, and Song in Kaluli Expression. By Steven Feld Rituals of Manhood. Male Initiation in Papua New Guinea. Edited by Gilbert H. Herdt Ways of Exchange: The Enga Tee of Papua New Guinea. By D. K. Feil Yena: Art and Ceremony in a Sepik Society. By Ross Bowden The Torres Strait Collections of A. C. Haddon: A Descriptive Catalogue. By David R. Moore The Great Museum. The Re-presentation of History. By Donald Horne Hunter-Gatherer Economy in Prehistory. A European Perspective. Edited by Geoff Bailey 1,000 Years of Gardening in New Zealand. By Helen Leach. A. H. & A. W. Reed, Wellington The Prehistory of New Zealand. By Janet Davidson Australia, The first twelve years. By Peter Taylor. George, Allen & Unwin The Discovery of Australia. The Charts & Maps of the Navigators & Explorers. By T. M. Perry The Secret Discovery of Australia. Portuguese ventures 250 years before Captain Cook. By Kenneth Gordon McIntyre Aboriginal Sites, Rights and Resource Development. Edited by R. M. Berndt Resource Development and the future of Australian Society. Edited by Stuart Harris and Geoff Taylor Power, Privilege and Prestige. Occupations in Australia. By Ann Daniel Australian Society: Introductory Essays. Fourth Edition. Edited by Sol. Encel and Lois Bryson Eclipse of Equality. Social Stratification in New Zealand. By David G. Pearson and David C. Thorns Indians in a White Australia: An Account of Race, Class and Indian Immigration to Eastern Australia. By Marie M. de Lepervanche Girmitiyas: The Origins of the Fiji Indians. By Brij V. Lal Women's Work and Women's Roles: Economics and Everyday Life in Indonesia, Malaysia and Singapore. Edited by Lenore Manderson A Celebration of Demons. Exorcism and the Aesthetics of Healing in Sri Lanka. By Bruce Kapferer Celebration. Studies in Festivity and Ritual. Edited by Victor Turner The Language of Easter Island. Its Development and Eastern Polynesian Relationships. By Robert Langdon and Darrell Tryon The Shaping of Man: Philosophical Aspects of Sociobiology. By Roger Trigg. Basil Blackwell The Ape's Reflexion. By Adrian Desmond. Blond and Briggs On Becoming Human. A Model of the Transition from Ape to Human and the Reconstruction of Early Social Life. By Nancy Makepeace Tanner Man, the Promising Primate: The Conditions of Human Evolution. By Peter J. Wilson Current Problems in Sociobiology. Edited by King's College Sociobiology Group 4 Anthropologists: An American Science in its Early Years. By Joan Mark Race, Language and Culture. By Franz Boas A Franz Boas Reader. The Shaping of American Anthropology, 1883–1911. Edited by George W. Stocking